PROSEDUR KERJA GUEST SERVICE ASSISTANCE MONTIGO RESORT NONGSA BATAM - Syahputra, Hafizh Wahyuda (RC-INSTITUT, 2019)
This study aims to determine the work procedures for the guest service assistance Montigo Resort Nongsa Batam. This type of research is descriptive research with qualitative methods. Data collection techniques used are through interviews, observation and documentation. The data analysis technique used is qualitative data analysis. From the results of the study found several things related to work procedures at the Montigo Resort Nongsa Batam Guest Service Assistance, namely: the main work of a Guest Service Assistance is often overlooked because it is not only focused on the GSA operational but also helps the operational in Front Office generally.